Coach-directed education is associated with injury-prevention behaviour in players: an ecological cross-sectional study. Issue 15 (25th November 2016) - Brown, James C; Gardner-Lubbe, Sugnet; Lambert, Michael Ian; van Mechelen, Willem; Verhagen, Evert
Abstract : Background/aim: Rugby union ('rugby') presents an above-average risk of injury to participants. BokSmart is a South African nationwide intervention that aims to reduce rugby-related injuries in players. This is achieved by educating coaches and referees to improve injury behaviour of players. Thus, the aim of this study was to assess if the receipt of injury-prevention education was associated with player behaviour. Methods: Junior (n=2279) and senior (n=1642) players, who attended merit-based South African Rugby tournaments (2008–2012), completed an anonymous questionnaire. Logistic regressions investigated if player injury-prevention behaviours were associated with the receipt of education on the same topic. Additionally, players' preferred sources of education were explored through frequency and χ 2 analyses. Results: Of the 16 injury-prevention behaviours, 12 (75%) were associated with receiving education on that topic. The four behaviours not associated with education were: warming-up (before training and matches), and avoiding heat and massage post injury. Of the seven possible sources of this education, the majority of players chose either coaches or physiotherapists as their preferred media. In comparison with junior players, more senior players chose physiotherapists instead of coaches for warming-up and cooling-down education. Conclusions: The results of this study support, to a large degree, the strategy of BokSmart —influence of player behaviour through coach education. However, these findings also suggest that BokSmart could target team physiotherapists in addition to coaches and referees with their safety education. Also, players might have different preferences for this education depending on their age.